Genetic and Ecological Relationships of Anastrepha ludens (Diptera: Tephritidae) Populations in Southern Mexico - Ruiz-Montoya, Lorena (Insects, 2020)
SIMPLE SUMMARY: The Mexican fruit fly, Anastrepha ludens, causes extensive damage to important agricultural commodities wherever it is found. Any effort to control or limit the damage caused by this pest requires a thorough understanding of the genetic makeup of the populations found in a particular area. Our study focused on flies found in the Soconusco region of southern Mexico. Flies in this region are typically found infesting different types of fruit trees that are either cultivated or naturally occurring. For our study, we collected male and female flies from four different types of fruit trees in several specific localities in the Mexican state of Chiapas. We analyzed the genetic makeup of a total of 725 flies in an attempt to look for differences that might be associated with the sex of the flies, the specific plants they were found on, or specific localities within the study area. We found a lot of genetic differences in flies from the various collections, but these were not strongly associated with different types of fruit trees or the specific collection site. From this, we concluded that the populations of flies from this entire region were largely similar. ABSTRACT: Knowledge of the influence of evolutionary factors that promote either the differentiation or cohesion of pest insect populations is critical for the improvement of control strategies. Here, we explore the extent to which genetic differentiation occurs between populations of the Mexican fruit fly, Anastrepha ludens, in association with four plant hosts (Citrus sinensis, C. paradisi, Mangifera indica and Casimiroa edulis) in the Soconusco region of Chiapas (Mexico). Using variants from six enzymatic loci, we obtained measures of genetic diversity for three sample arrangements: (1) by sex per locality, (2) by locality and (3) by host. The extent of genetic differentiation in populations was assessed using the Analyses of Molecular Variance (AMOVA) method for each array of samples, and moderate to high levels of genetic variation were observed between the sexes, as well as among localities and host plants. A Bayesian approach was then used to assess any population structure underlying the genetic data we obtained, but this analysis showed no significant structuring due to locality or host plant. We also considered whether the observed genotypic frequencies in male and females matched those expected under a hypothesis of random mating. Here we found significant deviations from expected genotypic frequencies, suggesting that sexual selection is acting on these populations. Overall, our results indicate that sexual selection, along with the presence of some heterogeneity in environments provided by both geographical factors and availability of host plants, has influenced the evolution of pest populations in this region of Mexico. Implications for area-wide pest management strategies are discussed.